Influence of Surface Electric Field on Exciton Photoluminescence of CdS: Self-Reversal of Spectral Lines - RAKOVICH, YURY (My University, 1995)
The structure of luminescence spectra of free excitons in CdS single crystals at T = 77 K is investigated. The dip formation is found in the top part of free A and B exciton resonant peaks of photoluminescence (PL) spectra after heating of the CdS crystals followed by fast cooling down to 77 K. Similar effects are observed when an external electric field is applied. It is shown that the structure of exciton PL spectra is due to self-absorption of resonance radiation in the near-surface layer with low exciton concentration. Our calculations demonstrate that the formation of an exciton concentration gradient may be caused by the influence of a surface electric field on the binding of electron-hole pairs to excitons. It is assumed that the increase of surface electric fields after heat treatment is caused by the thermostimulated adsorption of oxygen, which results in the formation of electron trap levels.
PUBLISHED
Keywords: Physics